2016
DOI: 10.3171/2015.5.jns1577
|View full text |Cite
|
Sign up to set email alerts
|

A prospective Phase II clinical trial of 5-aminolevulinic acid to assess the correlation of intraoperative fluorescence intensity and degree of histologic cellularity during resection of high-grade gliomas

Abstract: OBJECT There is evidence that 5-aminolevulinic acid (ALA) facilitates greater extent of resection and improves 6-month progression-free survival in patients with high-grade gliomas. But there remains a paucity of studies that have examined whether the intensity of ALA fluorescence correlates with tumor cellularity. Therefore, a Phase II clinical trial was undertaken to examine the correlation of intensity of ALA fluorescence with the degree of tumor cellularity. METHODS A single-center, prospective, single-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 36 publications
(39 reference statements)
3
110
0
Order By: Relevance
“…Phase 2 clinical trials also demonstrated a benefit in the use of 5-ALA during recurrent tumor treatment, even in patients previously treated with radio- and chemotherapy. 33, 34 Others have found that PpIX fluorescence may exceed the location of tumor tissue, resulting in false positives in 5-ALA guided surgical resection of recurrent malignant glioma, although surgical resection was still found to improve gross total resection, survival outcomes, or at worst not result in any additional neurological deficits in patients. 35-37 False positive labeling in recurrent glioma patients is likely the result of PpIX fluorescence in areas of reactive astrocytes and macrophages, 37 coagulation necrosis and vascular hyalinization.…”
Section: Non-targeted Fluorescent Imaging Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase 2 clinical trials also demonstrated a benefit in the use of 5-ALA during recurrent tumor treatment, even in patients previously treated with radio- and chemotherapy. 33, 34 Others have found that PpIX fluorescence may exceed the location of tumor tissue, resulting in false positives in 5-ALA guided surgical resection of recurrent malignant glioma, although surgical resection was still found to improve gross total resection, survival outcomes, or at worst not result in any additional neurological deficits in patients. 35-37 False positive labeling in recurrent glioma patients is likely the result of PpIX fluorescence in areas of reactive astrocytes and macrophages, 37 coagulation necrosis and vascular hyalinization.…”
Section: Non-targeted Fluorescent Imaging Agentsmentioning
confidence: 99%
“…40 A recent phase 2 clinical trial demonstrates that more than 60% of non-PpIX fluorescent biopsy tissue had tumor cells present, with a 37.7% negative predictive value. 33 In addition, limitations with current imaging systems may result in a failure to detect the labeling agent in weakly fluorescent PpIX positive infiltrative cells. 41 …”
Section: Non-targeted Fluorescent Imaging Agentsmentioning
confidence: 99%
“…Others 12,15,18,27 reported that MIB-1, an indicator of proliferation activity, and 5-ALA fluorescence were positively correlated. Widhalm et al .…”
Section: Discussionmentioning
confidence: 98%
“…Fluorescence was categorized as non-visible (negative) and visible (positive). 19,22 Positive fluorescence included mild (pink) and robust brightness (lava-like orange) 18 (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…New trials explore chemotherapy based on the dissection of the genomic landscape of GBM, chemotherapy active in other cancers that share signaling pathways active in GBM, new delivery methods to cover unresectable tumors, such as the Diffuse Intrinsic Pontine Glioma, an inoperable and very serious glioma in children (Buczkowicz, Bartels, Bouffet, Becher, & Hawkins, 2014; Buczkowicz & Hawkins, 2015; Grimm & Chamberlain, 2013; Jansen, van Vuurden, Vandertop, & Kaspers, 2012), anti-angiogenic agents (i.e., antagonists of VEGF) (Chinot et al, 2014; Fine, 2014; Gilbert et al, 2014; Gilbert, Sulman, & Mehta, 2014), the testing of novel surgical techniques to increase tumor resection with the aid of new imaging technologies (e.g., MRI (Bohman et al, 2010; Kubben et al, 2011), 5-Aminolevulinic acid (5-ALA (Hauser, Kockro, Actor, Sarnthein, & Bernays, 2015; Jaber et al, 2015; Lau et al, 2015)), Raman spectroscopy (Ji et al, 2013), as well as immunization (e.g., dendritic cells primed with unknown or known tumor antigens; with TLR agonists; with heat shock proteins) (Batich, Swartz, & Sampson, 2015; Finocchiaro & Pellegatta, 2014; Reardon et al, 2013; See et al, 2011; Weiss, Weller, & Roth, 2015). In summary, GBM remains one of the most lethal cancers, and the search for effective treatments needs to carry on.…”
Section: Towards Gene Therapy For Brain Tumors: Re-engineering the Brmentioning
confidence: 99%